DATOS SOBRE FAUNA DE MICROARTROPODOS, EN UN CICLO ANUAL EN DIFERENTES SUBSTRATOS DE UN BOSQUE DE NOTHOFAGUS PUMILIO - Covarrubias, Rene (Acta Entomológica Chilena, 2022)
Aerobic nhtroanhropods from a series of differenl substraía were studied, in a forest of Nothofagus puntillo. The forest is located in the "Torres del Paine" National Park and Biophere reserve, in the southernmost part of Chile (XII Región). Throughout one year samples were obtained monthly, from 5 different substraía in the forest. namely: litter, mineral soil, mosses growing on rocks, lichens growing on rocks and rotten wood. Bv means of Berlese-Tullgren funnels, 6 different higher taxa were found in sufficienl abundance, to allow analysis of variance. These laxa included 4 groups of miles: Oribalida ( = Cryptosiigmatid), Aclinedida, Tarsonemida and Camasida, and insects of the order Collembola (Poduromorpha, Entomobryomorpha). The taxa were found to differ signiftcantly bolh seasonally and according to substralum. The mosl important paltern was observed in movement belween the litter and subjacent mineral soil. suggesting that some taxa may migrate from one substratum to another. according to the time of year. Fifleen other laxa were found, but were only rarely collected and appeared irregularlv at different times of the vear and in differenl substraía.